2015
DOI: 10.1093/mnras/stu2467
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy And Mass Assembly (GAMA): mass–size relations of z < 0.1 galaxies subdivided by Sérsic index, colour and morphology

Abstract: We use data from the Galaxy And Mass Assembly (GAMA) survey in the redshift range 0.01 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
275
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 263 publications
(322 citation statements)
references
References 88 publications
45
275
2
Order By: Relevance
“…We adopt a simple power law, following Shen et al (2003) and Lange et al (2015), to fit the M − Re relation:…”
Section: − Re Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopt a simple power law, following Shen et al (2003) and Lange et al (2015), to fit the M − Re relation:…”
Section: − Re Relationsmentioning
confidence: 99%
“…This is most obvious in the Sérsic index -colour plane where the single component Sd and elliptical galaxies occupy distinct peaks with composite galaxies (S0abc) scattered between and around these peaks (see e.g., Driver et al 2006;Cameron et al 2009;Kelvin et al 2012;Lange et al 2015). These components have very different characteristics with spheroids typically having a featureless appearance and being pressure supported.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, different authors disagree on the extent of the reduction in sizes in various datasets. For example, in a recent study Lange et al (2015) revisited the GAMA sample with deeper NIR imaging data and found a smaller size decrease, ∼ 13% from g to K s band.…”
Section: Wavelength Dependence Of Light-weighted Galaxy Sizesmentioning
confidence: 99%
“…We also attempt to divide the sample in mass bins as in Lange et al (2015) to investigate the size change with wavelength for different masses. Lange et al (2015) showed that the size reduction decreases from ∼ 13% for local passive galaxies with log(M * /M ) = 10.0 to ∼ 11% for those with log(M * /M ) = 11.0.…”
Section: Wavelength Dependence Of Light-weighted Galaxy Sizesmentioning
confidence: 99%
“…Galaxy size is a basic observational property that is found to significantly vary with galaxy mass, color or star-formation activity, and redshift (Shen et al 2003;Ferguson et al 2004;Trujillo et al 2006;Elmegreen et al 2007;Williams et al 2010;Mosleh et al 2012;Ono et al 2013;van der Wel et al 2014;Lange et al 2015). These dependencies encode important information on the formation processes of galaxies of different types.…”
Section: Introductionmentioning
confidence: 99%